Effect of combustor inlet temperature and flame stabilizer pressure loss on weak extinction characteristics of premixed flames - Mustafa, Azeman (Faculty of Chemical & Natural Resources Engineering, 1993)
A can combustor was used to study the weak extinction characteristics of premixed swirling flames associated with two operating parameters, i.e. combustor inlet temperature and flame stabilizer pressure loss. The combustor was 76 mm in diameter and tested at a constant Mach number. High inlet temperature combustion was simulated using preheat air and variation in pressure loss across the flame stabilizer was accomplished by testing different swirler configurations. The test results show that increasing the combustor inlet temperature significantly widened the flame stability margin due to the increased shear layer ignition temperature. Increasing the flame stabilizer pressure loss improved the fuel distribution in the stabilising shear layer and consequently retarded the extension of the flame stability margin.